Morphological and molecular characterization of Bituminaria bituminosa accessions from South-East Spain and the Canary Islands - Muñoz A.; Ortiz-Dorda J.; Correal E. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
14 B. bituminosa accessions from South-East Spain and 3 from the Canary Islands were established in 1998 at La Alberca (Murcia). Molecular and morphological characterization tests were carried out to screen accessions with largest genetic diversity. Morphological traits of stems, leaves, inflorescences, flowers and seeds, correlated well with variability shown by PCR molecular analysis. Dendrogrames based on morphological traits and PCR analysis divided accessions into 6 homogeneous groups: 3 canarian (the more diverse) and 3 peninsular.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)